Bone repair access of BoneCeramic™ in 5-mm defects: study on rat calvaria - FABRIS,André Luis da Silva (2018)
Abstract Objective: The aim of this study was to evaluate the osteoconductive potential of BoneCeramic™ on bone healing in rat calvaria 5-mm defects. Material and Methods: A 5-mm calvaria bone defect was induced in three groups and the defect was not filled with biomaterial [Clot Group (CG)], autogenous bone (AG), or Bone Ceramic Group (BCG). Animals were euthanized after 14 or 28 days and the bone tissue within the central area of the bone defect was evaluated. Results were compared using ANOVA and Tukey test (p<0.05). Immunohistochemistry was performed using primary antibodies against osteocalcin, RUNX-2, TRAP, VEGF proteins, and 3-dimensional images of the defects in μCT were obtained to calculate bone mineral density (BMD). Results: In BCG, the defect was completely filled with biomaterial and new bone formation, which was statistically superior to that in the GC group, at both time-points (p<0.001 for 14 days; p=0.002 for 28 days). TRAP protein showed weak, RUNX-2 showed a greater immunolabeling when compared with other groups, VEGF showed moderate immunostaining, while osteocalcin was present at all time-points analyzed. The μCT images showed filling defect by BCG (BMD= 1337 HU at 28 days). Conclusion: Therefore, the biomaterial tested was found to be favorable to fill bone defects for the reporting period analyzed.